HUBUNGAN SARANA PRASARAN DAN MOTIVASI TERHADAP PENCAPAIAN PRESTASI OLAHRAGA SISWA SMA KOTA PANGKALPINANG - M RIZKAN KHADAVI; SAID AKHMAD MAULANA (PRODI PJKR UNIVERSITAS MUHAMMADIYAH MUARA BUNGO, 2020)
This study aims to determine whether there is a relationship between infrastructure and sports motivation towards sports achievement. subjects in this study were high school students in the City of Pangkalpinang. This research is a correlational research. This research resulted in a positive and significant relationship. The magnitude of the correlation coefficient is 0.498 from r table 0.254. The contribution of infrastructure and sports motivation to sports achievement is 24.8% and the correlation level is moderate or strong enough.